Against the Double Blackmail. Refugees, Terror and Other Troubles with the Neighbours - Gómez Castillo, Harvey; Jaramillo Villamizar, Oswaldo (Visión electrónica, 2019)
Against the Double Blackmail. Refugees, Terror and Other Troubles with the Neighbours US